Upregulated haptoglobin in classical monocytes serves as a diagnostic and immunological biomarker in myocardial infarction: a cross-sectional multi-omics study - Xu, Hongchen; Pan, Huibin; Mo, Chanjuan; Guo, Xueqi; Ji, Longfei; Shi, Danfei; Wang, Binyu; Li, Guodong; Li, Yong (Frontiers in Immunology, 2025)
BackgroundMyocardial infarction (MI) is one of the leading causes of death worldwide. Finding reliable diagnostic biomarkers and gaining a deeper understanding of their role in the immune microenvironment is of great significance for improving clinical prognosis.MethodThis study integrated multiple datasets from GEO (GSE141512, GSE95368, GSE269269) and TCGA data, and used various bioinformatics methods such as weighted gene co-expression network analysis (WGCNA), immune cell infiltration analysis, and single-cell RNA sequencing analysis to screen key genes related to the occurrence and development of myocardial infarction. We initially validated the results using a proteomic dataset (GSE95368) and clinical samples analyzed by qPCR. Critically, the dysregulation and diagnostic value of Haptoglobin (HP) were further confirmed in multiple independent external cohorts (GSE66360, and others.), solidifying its reliability as a biomarker.ResultThe study found that Haptoglobin (HP) is a key gene significantly upregulated in myocardial infarction, and it exhibits high diagnostic value (AUC=0.833) in the proteomic dataset (GSE95368). Single-cell sequencing analysis showed that HP is significantly highly expressed in classical monocyte of MI patients, and this finding was validated by qPCR experiments in clinically collected classical monocytes samples (p<0.05). Functional enrichment analysis implicated HP in immune responses and ferroptosis.ConclusionThe HP gene is a potential diagnostic biomarker for myocardial infarction, and its specific high expression in classical monocytes implies a potential role in the pathological process of myocardial infarction by regulating the immune microenvironment. This study provides a new research direction for the diagnosis and immune-targeted therapy of myocardial infarction, and has important clinical translational value.